2011
DOI: 10.1111/j.1948-7134.2011.00177.x
|View full text |Cite
|
Sign up to set email alerts
|

Host feeding responses of Aedes aegypti (L.) exposed to deltamethrin

Abstract: Escape responses of mated and unmated nulliparous Aedes aegypti mosquitoes were compared using three different concentrations of deltamethrin in the presence or absence of a live animal host using an excito-repellency (ER) test system. Both insecticide contact (excitation) and non-contact (repellency) test configurations were compared. For contact trials, mated mosquitoes showed similar escape movements among the three concentrations when host stimuli were absent. Significant differences in responses were seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Similarly, excito-repellency studies using lower concentrations of deltamethrin showed that mated Ae. aegypti exhibited significant differences in escape responses with and without hosts present [59]. This type of knowledge is critical to define the expected efficacy of a BGS trap in a repellent focused push-pull strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, excito-repellency studies using lower concentrations of deltamethrin showed that mated Ae. aegypti exhibited significant differences in escape responses with and without hosts present [59]. This type of knowledge is critical to define the expected efficacy of a BGS trap in a repellent focused push-pull strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Pyrethroid, one of the most prevalent insecticides, interacts with ion channels, which disrupt the transmembrane potentials, and damage the insect nervous system [7]. Deltamethrin (DM), a representative synthetic pyrethroid insecticide, is widely used for bed net impregnation and residual spraying for mosquito control [8], [9]. Widespread and improper use of insecticides has induced the development of insecticide resistance [10], [11], which has become the main obstacle for the mosquito-borne disease management [12][14].…”
Section: Introductionmentioning
confidence: 99%
“…Value of diazinon 96 h LC 50 was 0.8 mg/l for zebra fish (Brachydanio rerio) and it was eight mg/l for guppy (Poecilia reticulata) (Adedeji et al, 2008;Keizer et al, 1991). Getaway reaction of unmated and mated nulliparous Aedes aegypti mosquitoes were estimated using three different concentrations of deltamethrin in the presence or absence of a live organism host (Boonyuan et al, 2011). Although deltamethrin is thought to be lower toxic in field conditions due to its adsorption to sediment, these data are useful to potential ecosystem risk evaluation (Viran et al, 2003).…”
Section: Resultsmentioning
confidence: 99%